Icariside II ameliorates endothelial dysfunction by regulating the MAPK pathway via miR-126/SPRED1 in diabetic human cavernous endothelial cells - Lei H; Li H; Tian L; Li M; Xin Z; Zhang X; Guan R (Dove Medical Press, 2018)
Hongen Lei,1 Huixi Li,2 Long Tian,1 Meng Li,2 Zhongcheng Xin,2 Xiaodong Zhang,1 Ruili Guan2 1Department of Urology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing 100020, People’s Republic of China; 2Andrology Center, Peking University First Hospital, Peking University, Beijing 100034, People’s Republic of China Aim: The aim of the study was to investigate whether miR-126, a regulator of MAPK signaling via targeting sprouty-related EVH1 domain-containing protein 1 (SPRED1) mRNA, is involved in the process by which icariside II (ICA II) ameliorates endothelial dysfunction in human cavernous endothelial cells (hCECs) exposed to a diabetic-like environment.Materials and methods: Primary hCECs were isolated and divided into three groups, normal control, diabetes mellitus (DM), and DM treated with ICA II. The cell proliferation and migration abilities of the hCECs were examined. The expression levels of endothelial-related microRNAs and relative target mRNAs (SPRED1, phosphoinositol-3 kinase regulatory subunit 2, and vascular cell adhesion molecule 1) of miR-126 were determined by real-time PCR. The protein expression of endothelial nitric oxide synthase, receptor for advanced glycation end products, and SPRED1, and MAPK signaling activities was determined by Western blot analysis. In addition, miR-126 agomir and antagomir were used for transfection into hCECs to further testify the association between miR-126 and its targeting mRNA SPRED1.Results: hCECs induced with glucose plus advanced glycation end product-BSA showed a significant decrease in endothelial nitric oxide synthase, Ki-67, and miR-126 expression; a downregulated cell migration ability and an increased receptor for advanced glycation end products level. ICA II could partially reverse these changes. SPRED1 mRNA showed a contrary tendency with the miR-126-3p changes. The level of SPRED1 protein increased after the hCECs were induced with glucose plus advanced glycation end product-BSA, and ICA II could rescue its aberrant expression. In addition, the MAPK pathway was downregulated in the hCECs under diabetic conditions, and ICA II could partially enhance its signaling activities. miR-126 was obviously downregulated, and SPRED1 was accordingly upregulated after miR-126 antagomir transfection, while ICA II treatment could recover the expressions of both miR-126 and SPRED1. Moreover, the upregulation of miR-126 and the inhibition of SPRED1 were noticed in the diabetic hCECs by further transfection with miR-126 agomir.Conclusion: ICA II could ameliorate endothelial dysfunction by regulating the MAPK pathway via miR-126/SPRED1 in hCECs exposed to a diabetic-like environment, and ICA II might be a protective agent for endothelial function in diabetic ED. Keywords: human cavernous endothelial cells, endothelial dysfunction, miR-126, diabetes mellitus, icariside II